Microbial electrosynthesis of butyrate from carbon dioxide. Issue 15 (22nd January 2015) - Ganigué, R.; Puig, S.; Batlle-Vilanova, P.; Balaguer, M. D.; Colprim, J.
Abstract : This work proves for the first time the bioelectrochemical production of butyrate from CO2 as a sole carbon source. Abstract : This work proves for the first time the bioelectrochemical production of butyrate from CO2 as a sole carbon source. The highest concentration of butyrate achieved was 20.2 mMC, with a maximum butyrate production rate of 1.82 mMC d −1 . The electrochemical characterisation demonstrated that the CO2 reduction to butyrate was hydrogen driven. Production of ethanol and butanol was also observed opening up the potential for biofuel production.